2002
DOI: 10.1016/s0167-2738(02)00131-5
|View full text |Cite
|
Sign up to set email alerts
|

Sm0.5Sr0.5CoO3 cathodes for low-temperature SOFCs

Abstract: The electrochemical properties of the interfaces between an Sm 0.2 Ce 0.8 O 1.9 (samaria-doped ceria, SDC) electrolyte and porous composite cathodes consisting of Sm 0.5 Sr 0.5 CoO 3 (SSC) and SDC have been investigated in anode-supported single cells at low temperatures (400 -600 jC). The bilayer structures of the SDC electrolyte films (25 Am thick) and the NiO -SDC anode supports were formed by co-pressing and subsequent co-firing at 1350 jC for 5 h. The effect of composition, firing temperature, and microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
265
3
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 626 publications
(284 citation statements)
references
References 17 publications
11
265
3
5
Order By: Relevance
“…LaSrGaO 4 and LaSrGa 3 O 7 phases again were present in small amount. The XRD scan of the composite SSC-SDC powder gave the expected peaks associated with SSC and SDC (20). There were LaSrGaO 4 and LaSrGa 3 O 7 precipitates detected when the composite cathode SSC-SDC/LSGMC was calcined on LSGM.…”
Section: Resultsmentioning
confidence: 97%
“…LaSrGaO 4 and LaSrGa 3 O 7 phases again were present in small amount. The XRD scan of the composite SSC-SDC powder gave the expected peaks associated with SSC and SDC (20). There were LaSrGaO 4 and LaSrGa 3 O 7 precipitates detected when the composite cathode SSC-SDC/LSGMC was calcined on LSGM.…”
Section: Resultsmentioning
confidence: 97%
“…Many perovskite oxides (e.g. SCFN and LSCF) have been studied and developed as the mixed ionic and electronic conductors (MIEC) that can provide the path for transferring both electrons and ions to improve the electrochemical performance of the IT-SOFCs cathode [7][8][9][10][11][12][13][14] . Moreover, recent studies have shown the potential of some perovskite related structures such as GdBaCo 2 O 5+δ and SmBaCo 2 O 5+x with layered and doubled structures, respectively, for operation at reduced temperatures due to their low activation energy.…”
Section: Research Objectives and Motivationmentioning
confidence: 99%
“…A 800ºC para o metano como combustível, a tensão foi constante a partir de uma corrente de 5 mA, não sendo possível a coleta de dados entre esta corrente e dados de circuito aberto. Essa célula de PaCOS unitária mostrou desempenho para a produção de energia elétrica comparativo a dados reportados na literatura [67]. Além disto, o gráfico de potência apresenta uma estimativa preliminar para o desempenho da célula utilizando hidrogênio e operando a 800ºC.…”
Section: Energia De Ligação Evunclassified